A Study on Product Innovation Portfolio and Customer Value Creation: Bridging Entrepreneurial Risk-Taking Orientation and Marketing Performance - Killa, Maklon Felipus (ASEAN Marketing Journal, 2021)
The aims of this study is to investigate the role of product innovation portfolio and customer value creation in bridging the gap of research entrepreneurial risk-taking orientation and marketing. Wood crafts firms that are in the city of Bandung, Yogyakarta and Solo which has been regarded as a creative city in Indonesia used as a sample. Sampling was done by using a combination of purposive sampling and convenience sampling. Data were collected using a questionnaire given directly to the respondent. The total data used for analysis about 172 respondents. Data analysis used in this research is Structural Equation Modeling (SEM) with the AMOS program. The results show that product innovation portfolio serves as mediating on the relationship between entrepreneurial risk-taking orientation and marketing performance. Futhermore, the results also find that customer value creation has a positive effect on marketing performance.